Infancy predictors of preschool and post‐kindergarten executive function. Issue 5 (12th June 2012) - Kraybill, Jessica H.; Bell, Martha Ann
Abstract Little is known about factors that promote optimal development of executive function (EF) skills. The focus of this study was associations among early maternal behaviors, infant frontal brain electrical activity, and child EF at age 4 and following kindergarten. Infant frontal electroencephalogram was collected from 56 infants at 10 months of age and maternal positive affect was observed. Children completed EF measures in the research laboratory at age 4; parental‐reported EF was obtained following children's kindergarten year. Maternal positive affect and infant frontal brain electrical activity measured when the children were 10 months jointly and uniquely predicted both preschool and post‐kindergarten EF. Findings suggest parenting behavior and brain development in infancy are precursors of later self‐regulatory EF abilities. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 530–538, 2013